Steroid resistance in asthma: mechanisms and potential therapies - Adcock, Ian (Henry Stewart Talks, 2022)
Asthma pathophysiology, The use of corticosteroids, Reasons for steroid resistance or insensitivity, Methods to improve steroid efficacy in severe asthma, Mechanisms that induce steroid insensitivity, Problems occurring due to oxidative stresses, Novel anti-inflammatory approaches